Genome Report—A Genome Sequence Analysis of the RB51 Strain of Brucella abortus in the Context of Its Vaccine Properties. Issue 4 (1st April 2020) - Bricker, Betsy; Goonesekere, Nalin; Bayles, Darrell; Alt, David; Olsen, Steven; Vrentas, Catherine
Abstract: The RB51 vaccine strain of Brucella abortus, which confers safe and effective protection of cattle from B. abortus infection, was originally generated via serial passage of B. abortus 2308 to generate spontaneous, attenuating mutations. While some of these mutations have been previously characterized, such as an insertional mutation in the wboA gene that contributes to the rough phenotype of the strain, a comprehensive annotation of genetic differences between RB51 and B. abortus 2308 genomes has not yet been published. Here, the whole genome sequence of the RB51 vaccine strain is compared against two available 2308 parent sequences, with all observed single nucleotide polymorphisms, insertions, and deletions presented. Mutations of interest for future characterization in vaccine development, such as mutations in eipA and narJ genes in RB51, were identified. Additionally, protein homology modeling was utilized to provide in silico support for the hypothesis that the RB51 capD mutation is the second contributing mutation to the rough phenotype of RB51, likely explaining the inability of wboA -complemented strains of RB51 to revert to a smooth phenotype.